THE CONTRIBUTION OF PRINCIPAL TRANSFORMATIONAL LEADERSHIP, WORK MOTIVATION, THROUGH SATISFACTION WITH OCB TEACHERS - Febriani, Heri; Aslamiah; Saleh , Muhammad; Ishak (Journal of K6, Education and Management, 2019)
The purpose of this research is to analyze the influence of leadership, motivation, and satisfaction on Organizational Citizenship Behavior (OCB). It uses a quantitative approach with a population of 114 taken by proportionate sampling from 159 individuals in 6 Tanjung Redeb Junior High School in East Kalimantan. Data were collected using a questionnaire and tested for validity and reliability, the resulting regression model has been tested classic assumptions including normality, multicollinearity, linearity, and heteroscedasticity tests, then analyzed with descriptive statistics and path analysis through calculations using SPSS. The results showed that there was an influence of leadership motivation on satisfaction with OCB. Generally, satisfaction was the intermediary between the leadership and OCB; leadership and motivation.